2007
DOI: 10.1029/2007gl029629
|View full text |Cite
|
Sign up to set email alerts
|

Melt distribution beneath a young continental rift: The Taupo Volcanic Zone, New Zealand

Abstract: Taupo Volcanic Zone (TVZ) is a zone of intense volcanism and rifting associated with the subduction of the Pacific Plate beneath the continental crust of New Zealand's North Island. An image of the conductivity structure beneath the central part of the TVZ has been constructed using 2‐D inverse modeling of magnetotelluric data. A rapid increase in conductivity at a depth of 10 km beneath the TVZ, ∼3 km beneath the base of the seismogenic zone but well above the base of the quartzo‐feldspathic crust (∼16 km), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 25 publications
8
91
0
Order By: Relevance
“…Ascent into the shallow crust encompasses both repeated sill intrusion and multiple, interacting dykes (e.g., Hamling et al, 2010). Rift zones are extensively intruded by interconnected lenses of melt (e.g., Heise et al, 2007), but InSAR measurements have nevertheless shown the importance of repeated deformation originating beneath volcanoes and of repeated sill intrusion, which also seem to play a role in rifting events. For example, uplift attributed to sill intrusion at Alu and Gabho in Ethiopia preceded the Alu-Dalafilla and Dabbahu rifting episodes, respectively , and similarly a deformation source beneath dormant Gelai volcano was active during rifting in Tanzania .…”
Section: Insights From Global Insar Volcano Deformation Measurementsmentioning
confidence: 99%
“…Ascent into the shallow crust encompasses both repeated sill intrusion and multiple, interacting dykes (e.g., Hamling et al, 2010). Rift zones are extensively intruded by interconnected lenses of melt (e.g., Heise et al, 2007), but InSAR measurements have nevertheless shown the importance of repeated deformation originating beneath volcanoes and of repeated sill intrusion, which also seem to play a role in rifting events. For example, uplift attributed to sill intrusion at Alu and Gabho in Ethiopia preceded the Alu-Dalafilla and Dabbahu rifting episodes, respectively , and similarly a deformation source beneath dormant Gelai volcano was active during rifting in Tanzania .…”
Section: Insights From Global Insar Volcano Deformation Measurementsmentioning
confidence: 99%
“…There are many examples in the literature where conductive anomalies have been quantitatively interpreted in terms of partial melt (e.g., Pous et al 1995;Brasse et al 2002;Heise et al 2007;Didana et al 2014). The melt (or fluid) fraction can be directly calculated from the bulk resistivity using mixing laws (assuming the melt conductivity is known).…”
Section: Meltsmentioning
confidence: 99%
“…Measurements have, however, been made close to the field and across the TVZ. These measurements provide images of the resistivity structure at great depth (∼30 km) from which can be deduced the thermal conditions beneath the geothermal systems of the TVZ (Ogawa et al, 1999;Ingham, 2005;Heise et al, 2007).…”
Section: Deep Structure and Heat Sourcesmentioning
confidence: 99%